PERAN BADAN PERMUSYAWARATAN DESA DALAM PERENCANAAN PEMBANGUNAN DESA MEDALEM - Rossilahi Chasanah; Ahmad Riyadh (Halu Oleo University, 2024)
This study will examine the role of the Village Consultative Body (BPD) in the development planning of Medalem Village using Soerjono Soekanto's role theory. The purpose of this study is to describe the role of the Village Consultative Body (BPD) in the development planning of Medalem Village according to the six indicators of Soerjono Soekanto's role theory. The research method is descriptive qualitative, with data collection techniques through observation and interviews. The results of this study show that the role of the BPD of Medalem Village has not been fully implemented. It is proven from the results obtained that 3 of the 6 indicators of Soekanto's role theory still have problems, namely (1) role conflict in the form of unclear information delivery between the BPD; (2) rights and obligations in the form of BPD supervision are only formalities without in-depth evaluation; and (3) social expectations in the form of the absence of several BPD members without clear explanation.